Berbagai Ukuran Moral Untuk Mengembangkan Semangat Profesionalisme - Samin, Rumzi (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2016)
The touch of a moral element must be higher than the minimum intellectual or there is a balance between morality and professionalism. Ethics is always associated with human customs or habits, whether it is a good practice as well as deviant or bad habits, how people should behave and act in interacting with other humans. In the reality of social life, all societies have moral rules that allow or prohibit certain acts. Professionalism is a demand that can not be avoided if the government wants a good performance, but the meaning of professionalism is only interpreted in terms of skills (skillful) solely so that the various education and training is only intended to develop his skills. Difficult to deny that a high skill without coupled high morality anyway does not mean anything. For that we need to have a strategy efforts should be made so that the apparatus of professionalism and morality in a balanced manner. The strategy should be designed to improve the performance of the government is the balancing act between the development of professionalism and morality bureaucratic apparatus.